A wireless closed-loop optogenetic neurostimulation system with 32-channel neural recording - Qi, Jing (My University, 2023)
A brain-machine interface is an interactive interface that communicates between the brain and a machine. A closed-loop brain-machine interface collects and analyzes neural signals from the brain and modulates the nervous system based on the analysis of results. Neuromodulation is a way of regulating the function of the brain by stimulating or inhibiting neural activity through the application of external stimuli. Among the various neuromodulation techniques, optical stimulation is highly directional, and has little thermal effect and impact on neuro-electrical recordings, allowing for inhibitory and excitatory bi-directional stimulation. Closed-loop optogenetic stimulation systems contain both stimulation and perception. It is more precise than traditional electrical stimulation and is primarily used in neural prosthetics research, rehabilitation therapy, neural circuit research, and chronic disease treatment. With the development of wireless technology, flexible device processing, low-power technology, etc., the closed-loop optogenetic stimulator is also gradually developing toward wireless design, low-power consumption, miniaturization, and good biocompatibility. In this thesis, we study and discuss the critical technologies of wireless closed-loop optogenetic systems, summarize the hardware and software frameworks of a wireless closed-loop optogenetic stimulation system, and carry out both the design and implementation of a wireless closed-loop optogenetic stimulation system. The designed system consists of a device side and a receiver side. The device side uses a 32-channel flexible electrode as the nerve electrode, a high-precision bandwidth-adjustable sampling-rate-adjustable RHD2132 chip as the analog front-end to filter and amplify the signal, and a low-power Bluetooth chip to achieve wireless communication. After receiving the wireless neural signal on the upper computer side, it uses various signal processing methods such as band stop filter, threshold detection, and low-pass filtering. Wireless optical stimulation commands are set and sent from the upper computer side. The optical stimulation parameters include frequency, duty cycle, and channel of stimulation. The upper computer user interface is developed to realize a closed-loop system. One of the features of the system designed in this thesis is the ability to perform recording, wireless transmission, signal processing, and presentation of 32 channels of local field potentials in real time. The closed-loop control can be achieved by setting up optical stimulation parameters in the user interface. The design also uses flexible electrodes to reduce insertion damage during implantation therefore good biocompatibility can be achieved. The system is wireless, has low power consumption, and is miniaturized in size. This wireless, closed-loop optical stimulator can be implanted to monitor the brain signals and control the stimulation for a long time. It is suitable for the treatment of chronic disease, suppression of acute disease onset, neural loop research, neural repair, and other application scenarios.
Keywords: closed-loop brain-computer interface, brain neural signals, optical stimulation, low-energy Bluetooth